Thornton, John - The Kongolese Saint Anthony Dona Beatriz Kimpa Vita and the Antonian Movement, 1684-1706. Cambridge University Press, 1998 - Gonçalves, António Custódio; Santos, Maciel Morais (Africana Studia, 2020)
.